Penerapan Pembelajaran Berdeferensiasi Dalam Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Silvia Meirisa (Innovative: Journal Of Social Science Research, 2023)
This research is a Classroom Action Research (CAR) adopted from Kemmis and Taggart. This study aims to improve learning outcomes in learning mathematics. The research was conducted at SDN 217/III Talang Kemuning, Bukit Kerman District, Kerinci Regency, Jambi Province, in the even semester of the 2022/2023 school year. The subjects in this study were 24 grade IV students consisting of 10 male students and 14 female students. The procedure in this study follows the PTK flow, starting from planning, action, observation, and reflection. Data collection in this study was through observation sheets obtained through observations of the learning process and through the results of evaluation tests at the end of each learning cycle using test instruments. The results of the research carried out in cycle I obtained a completeness score of 66.7%, which indicated that there were 16 students who met KKM 75 and 8 students who did not meet KKM. In cycle II, a completeness score of 91.7% was obtained, which indicated that there were 22 students who met the KKM and 2 students had not met the KKM. Based on the research results, it can be concluded that the application of differentiated learning in mathematics learning can improve student learning outcomes.